The glycosyltransferase UGT76E1 significantly contributes to 12-O-glucopyranosyl-jasmonic acid formation in wounded Arabidopsis thaliana leaves - Haroth, Sven (J Biol Chem, 2019)
Jasmonoyl-isoleucine (JA-Ile) is a phytohormone that orchestrates plant defenses in response to wounding, feeding insects, or necrotrophic pathogens. JA-Ile metabolism has been studied intensively, but its catabolism as a potentially important mechanism for the regulation of JA-Ile–mediated signaling is not well-understood. Especially the enzyme(s) responsible for specifically glycosylating 12-hydroxy-jasmonic acid (12-OH-JA) and thereby producing 12-O-glucopyranosyl-jasmonic acid (12-O-Glc-JA) is still elusive. Here, we used co-expression analyses of available Arabidopsis thaliana transcriptomic data, identifying four UDP-dependent glycosyltransferase (UGT) genes as wound-induced and 12-OH-JA–related, namely, UGT76E1, UGT76E2, UGT76E11, and UGT76E12. We heterologously expressed and purified the corresponding proteins to determine their individual substrate specificities and kinetic parameters. We then used an ex vivo metabolite-fingerprinting approach to investigate these proteins in conditions as close as possible to their natural environment, with an emphasis on greatly extending the range of potential substrates. As expected, we found that UGT76E1 and UGT76E2 are 12-OH-JA-UGTs, with UGT76E1 contributing a major in vivo UGT activity, as deduced from Arabidopsis mutants with abolished or increased UGT gene expression. In contrast, recombinant UGT76E11 acted on an unidentified compound and also glycosylated two other oxylipins, 11-hydroxy-7,9,13-hexadecatrienoic acid (11-HHT) and 13-hydroxy-9,11,15-octadecatrienoic acid (13-HOT), which were also accepted by recombinant UGT76E1, UGT76E2, and UGT76E12 enzymes. UGT76E12 glycosylated 12-OH-JA only to a low extent, but also accepted an artificial hydroxylated fatty acid and low amounts of kaempferol. In conclusion, our findings have elucidated the missing step in the wound-induced synthesis of 12-O-glucopyranosyl-jasmonic acid in A. thaliana.